The Unmet Needs of the Diagnosis, Staging, and Treatment of Gastrointestinal Tumors - Halama, Niels; Haberkorn, Uwe (Seminars in nuclear medicine, 2020)
New scientific insights in cancer biology and immunobiology have changed the clinical practice of medical oncology in recent years. The molecular stratification of solid tumors has led to improved clinical outcomes and is a key part in the diagnostic workup. Beyond mutational spectra (like Rat sarcoma [RAS] mutations or tumor mutational burden), the investigation of the immunological microenvironment has attracted more efforts. Especially as immunotherapies have changed the standard treatment for some solid tumors dramatically and have become an important part of routine oncology, also for gastrointestinal tumors. Still only a subgroup of patients benefits from immunotherapy in gastrointestinal tumors with prominent examples from colorectal, pancreatic or gastric cancer. Not only microsatellite instability as a marker for response to immunotherapy has shown its utility, there plenty of other approaches currently being investigated to better stratify and understand the microenvironment. But these insights have not translated into clinical utility. Reasons for this are limited technical capabilities for stratification and for coping with heterogeneity of tumor cells and the microenvironment as such. So the situation for gastrointestinal tumors has shown mainly progress for a subgroup of immunotherapy-receptive tumors (eg, microsatellite instability), but advances for the remaining majority have been in the area of stratification and combinatorial therapies, including approaches without chemotherapy. Molecular stratification (eg, B-Rapidly Accelerated Fibrosarcoma [BRAF] V600E mutation in colorectal cancer or NRG1 fusions in Kirsten-rat sarcoma (KRAS) Wild-Type Pancreatic Cancer) has clearly improved the possibilities for directed therapies, but there is a plethora of clinical situations where further developments are needed to improve patient care. Finding these areas and identifying the technical approach to unravel the complexities is the next decisive step. Here the recent advances are summarized and an outlook on possible diagnostic and treatment options in areas of unmet need is given with the context of new molecular imaging possibilities and cutting edge advances in nuclear medicine.